Pendampingan Lesson Study: Meningkatkan Pelaksanaan Pembelajaran dengan Pendekatan Scientific Guru SD Muhammadiyah 3 Gresik - Arya Setya Nugroho; Nataria Wahyuning Subayani (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
This devotion was accomplished because it was found that the implementation of learning with the 2013 curriculum had difficulties, many teachers did not yet understand how to learn the scientific approach. In addition, Muhammadiyah 3 Gresik Elementary School Teacher experience weaknesses in the development of assessment sheets and student worksheets (LKS) using only LKS from related agencies or certain publishers who collaborate with schools. The solution provided is assistance and implementation of a Lesson study with a Scientific approach. The results of the implementation of learning showed an increase from cycle I with an average of 56 to 88 in cycle II. Learning is much more interesting and vibrant. When learning the teacher freely controls the class so that students can study seriously but with a pleasant atmosphere. Thus it can be concluded that lesson study assistance carried out in grade 3 of Muhammadiyah 3 Gresik Elementary School was successful as expected. Keywords: Assistance, lesson study, scientific, elementary school.